2001
DOI: 10.1348/000709901158596
|View full text |Cite
|
Sign up to set email alerts
|

Predicting early grade retention: A longitudinal investigation of primary school progress in a sample of rural South African children

Abstract: Results corroborate those of developed world studies, in showing that early academic achievement is a strong predictor of retention. In addition, they highlight the importance of early curriculum mastery--rather than broader cognitive skills--for smooth progression through school.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
37
0
3

Year Published

2002
2002
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(42 citation statements)
references
References 30 publications
2
37
0
3
Order By: Relevance
“…Some researches indicate that school readiness is associated with learning, attending to school, developing further skills and academic success or failure (Jaramillo & Tietjen, 2001;Pianta & McCoy 1997;Reynolds 2001;Rouse, Brooks-Gunn, & Mclanahan, 2005 obtained from applications showed that children develop a positive attitude towards school and their academic skills increase (Liddell & Rae, 2001;Stith, Gorman, & Choudhury 2003;Nonoyama, Tarumi, & Bredenberg, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Some researches indicate that school readiness is associated with learning, attending to school, developing further skills and academic success or failure (Jaramillo & Tietjen, 2001;Pianta & McCoy 1997;Reynolds 2001;Rouse, Brooks-Gunn, & Mclanahan, 2005 obtained from applications showed that children develop a positive attitude towards school and their academic skills increase (Liddell & Rae, 2001;Stith, Gorman, & Choudhury 2003;Nonoyama, Tarumi, & Bredenberg, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Though the evidence supporting early childhood education in developed countries is strong, it cannot be assumed that this evidence translates directly to the context of sub-Saharan African countries. However, several recent studies conducted in Kenya, Zanzibar and Uganda (Malmberg, Mwaura, & Sylva, 2011;Mwaura, Sylva, & Malmberg, 2008); Botswana (Taiwo & Tyolo, 2002);South Africa (Liddell & Rae, 2001); and Guinea and Cape Verde (Jaramillo & Tietjen, 2001) support the argument that ECE is just as important in preparing African children for later academic success as it is for those living in the developed world.…”
Section: Introductionmentioning
confidence: 99%
“…In the past, because of fiscal considerations, many provincial Departments of Education in China (and other developing countries) abolished retention or set maximum limits on the percentage of students in each cohort who could be retained during their primary school years (Guangming Daily, 2000;Liddell and Rae, 2001). For example, in Gansu province in China, primary school principals were instructed to retain no more than 3% of the students in any of the six grades that constitute elementary education (Guangming Daily, 2000).…”
Section: Introductionmentioning
confidence: 99%